Concentrations and health risks assessment of heavy metals in cigarettes within Baghdad city - M. Haleem, Azhar; A. Amin, Sahar (International Journal of Physical Research, 2021)
The risks associated with smoking can be due to the inhalation of toxic substances like heavy metals and polycyclic aromatic hydrocarbons (PAHs) that can be released during tobacco burns. In the present study we measured lead Pb and three other metals (cadmium Cd; Chrome Cr; and Zinc Zn) by flame atomic absorption spectroscopy (FAAS). In a twenty-five brands of cigarettes, assessing potential related health risks estimated intakes of these metals. The Related Cancer Risk (RCR) and Average Daily Intake (ADI) were calculated. The results revealed that the average values of Pb, Cd, Cr and Zn concentrations were (4.56, 0.39, 3.31 and 1.36) Î¼g/g respectively. The total value of these four metals is greater than the range of cancer risk specified by USEPA.Â Â